Controlled Fabrication of Native Ultra-Thin Amorphous Gallium Oxide From 2D Gallium Sulfide for Emerging Electronic Applications - Nicolosi, Valeria (My University, 2024)
Oxidation of 2D layered materials has proven advantageous in creating oxide/2D material heterostructures, opening the door for a new paradigm of low-power electronic devices. Gallium (II) sulfide (β-GaS), a hexagonal phase group III monochalcogenide, is a wide bandgap semiconductor with a bandgap exceeding 3 eV in single and few-layer form. Its oxide, gallium oxide (Ga2O3), combines a large bandgap (4.4–5.3 eV) with a high dielectric constant (≈10). Despite the technological potential of both materials, controlled oxidation of atomically-thin β-GaS remains under-explored. This study focuses on the controlled oxidation of β-GaS using oxygen plasma treatment, addressing a significant gap in existing research. The results demonstrate the ability to form ultrathin native oxide (GaSxOy), 4 nm in thickness, upon exposure to 10 W of O2, resulting in a GaSxOy/GaS heterostructure where the GaS layer beneath remains intact. By integrating such structures between metal electrodes and applying electric stresses as voltage ramps or pulses, their use for resistive random-access memory (ReRAM) is investigated. The ultrathin nature of the produced oxide enables low operation power with energy use as low as 0.22 nJ per operation while maintaining endurance and retention of 350 cycles and 104 s, respectively. These results show the significant potential of the oxidation-based GaSxOy/GaS heterostructure for electronic applications and, in particular, low-power memory devices.
Keywords: oxide/2D material heterostructures; hexagonal phase group III monochalcogenide; high dielectric constant; oxide/2D material heterostructures; hexagonal phase group III monochalcogenide; high dielectric constant